2014
DOI: 10.1063/1.4875802
|View full text |Cite
|
Sign up to set email alerts
|

Precursory signatures of protein folding/unfolding: From time series correlation analysis to atomistic mechanisms

Abstract: Folded conformations of proteins in thermodynamically stable states have long lifetimes. Before it folds into a stable conformation, or after unfolding from a stable conformation, the protein will generally stray from one random conformation to another leading thus to rapid fluctuations. Brief structural changes therefore occur before folding and unfolding events. These short-lived movements are easily overlooked in studies of folding/unfolding for they represent momentary excursions of the protein to explore … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 91 publications
0
2
0
Order By: Relevance
“…Regarding the numbers of reference configurations, it is suggested that the similarity functions be statistically analyzed. The shape similarity technique has also been applied to a large system, namely, the folding of a transthyretin peptide . Twelve similarity functions were generated for substructures, which were characterized based on residues, and a cross‐correlation analysis was performed to evaluate folding dynamics.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the numbers of reference configurations, it is suggested that the similarity functions be statistically analyzed. The shape similarity technique has also been applied to a large system, namely, the folding of a transthyretin peptide . Twelve similarity functions were generated for substructures, which were characterized based on residues, and a cross‐correlation analysis was performed to evaluate folding dynamics.…”
Section: Resultsmentioning
confidence: 99%
“…Ultimately, shape similarity is applicable not only for finite‐size clusters but also for any type of molecule that presents shape. The dynamical analysis of the folding and unfolding of the peptide molecule was conducted using the same technique . The proposed method should become a powerful tool for studying nanostructures and biological systems.…”
Section: Discussionmentioning
confidence: 99%